Pengaruh Citra Bank, Kualitas Pelayanan, Kepercayaan Nasabah, Penanganan Keluhan, Dan Kepuasan Terhadap Loyalitas Nasabah Pada Bank Sumsel Babel Kantor Capem Syariah UIN Raden Fatah Palembang - Batin, Mail Hilian (MALIA: Journal of Islamic Banking and Finance, 2019)
The purpose of this study is to determine the effect of variable bank image, service quality, customer trust, handling complaints, and satisfaction with customer loyalty. Islamic Bank SUMSEL BABEL of UIN Raden Fatah Palembang. The Source of Data taken is primary data through questionnaires to 100 respondents using purposive sampling. The results showed that the bank image variable, service quality, customer trust, and complaint handling had a simultaneous effect on customer loyalty, as evidenced by the significance value of 0,000 <0,05. While the partial test can be concluded that the bank image variable (X1) has a positive effect on customer loyalty (Y), this is evidenced by a significance value of 0.006 <0.05. Service quality variable (X2) does not affect customer loyalty (Y), this is evidenced by the significance value of 0.997> 0.05. The variable customer trust (X3) has a positive effect on customer loyalty (Y), this is evidenced by the significance value of 0.003 <0.05. The complaint handling variable (X4) has a positive effect on customer loyalty (Y), this is evidenced by the significance value of 0.009 <0.05. Satisfaction variable (X5) has a positive effect on customer loyalty (Y), this is evidenced by the significance value of 0.021 <0.05